Analysis Audit Report Lag in Industry - Indriyani; Damayanti; Hendra Prasetyo (PT. Altaf Publishing Corp, 2025)
Lateness delivery audit report can cause lateness delivery report finance. The purpose of the study is To test How internal company factors, such as profitability, size of the company, leverage, audit opinion, and position dual director, influence the lateness delivery of audit reports. A number of characteristics, including profitability, size of the company, leverage, position of concurrent directors, and an audit opinion have been linked with the lateness of delivery of the internal audit report study previously. Companies in each​ industry are listed on the Stock Exchange. For the period 2020–2021, there is a population study. Quantitative data in form number used in study This. Report finance 2020–2021 annual release and listed on the Indonesia Stock Exchange (BEI) via the website www.idx.co.id becomes data source. Based on results testing, the most influential variables to audit report lag in the sector industry are variable profitability, Company size, and audit opinion, This because exists different characteristics between sectors.